Functional properties of skim milk powder from online and physical retail markets in Metro Manila and Cebu City - Buenaobra, Chloe Bianca M.; Francisco, Maria Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
Milk is considered an "ideal food" because of its good nutritional value. It can be processed into more shelf-stable products such as skim milk powder (SMP). However, SMP is prone to adulteration as milk is the second most adulterated food product worldwide. Therefore, it is essential to safeguard the quality these milk products being imported. Thus, this study was conducted to evaluate the functional properties of SMP in major Philippine markets by investigating their quality, determine compliance with industry standards, and draw implications about their handling. Twenty-one samples of SMP were purchased from sellers in Metro Manila and Cebu and evaluated based on their flowability, heat stability, emulsifying capacity, emulsifying stability, and solubility. Results showed that despite only one of twenty-one samples was considered to be authentic SMP, many samples performed well across all experiments: 14 exhibited good emulsifying properties and heat stability, 15 showed good solubility indexes, and all had fair to excellent flowability. Therefore, although the products not truly SMP, it is likely that consumers still purchase them because their performance is passable for how they would use the powders. Moving forward, the Philippine Food and Drug Administration can make sure that imported and repacked SMP is of declared quality by conducting frequent and thorough audits.
Thesis Classification: F
Thesis
Includes bibliographical references and appendices.
Keywords: Dried skim milk -- Philippines